First-Line Anti-Tubercular Drug Resistance of Mycobacterium tuberculosis in IRAN: A Systematic Review - Pourakbari, Babak; Mamishi, Setareh; Mohammadzadeh, Mona; Mahmoudi, Shima (Frontiers in Microbiology, 2016)
Background: The spread of drug-resistant tuberculosis (TB) is one of the major public health problems in the world. Surveillance of anti-TB drug resistance is important for monitoring of TB control strategies. The occurrence of drug resistance, particularly multi-drug resistance Mycobacterium tuberculosis (MDR), defined as resistance to at least rifampicin (RIF) and isoniazid (INH), has become a significant public health dilemma. However, the status of drug-resistance TB in Iran has been reported inconsistently. Therefore, the aim of this study was to summarize reports on first-line anti-tubercular drug resistance of M. tuberculosis in Iran. Material and Methods: We systematically reviewed published studies on drug-resistant M. tuberculosis in Iran. Search terms ̎Mycobacterium tuberculosis susceptibility ̎ and ̎Mycobacterium tuberculosis resistant ̎ were used in PubMed, Google Scholar, Magiran, IrMedex and SID. Results: Fifty- two eligible articles, published during 1998-2014, were included in this review. Most studies were conducted in Tehran. The most common laboratory method was used for anti-drug resistant of M. tuberculosis was Agar proportion. The average prevalence of resistant against INH in Tehran was 26%, RIF 23%, streptomycin (SM) 22.5% and ethambotol (EMB) 16% by Agar proportion method. In general, resistance to INH was more common than RIF, SM and EMB in Tehran. The average prevalence of resistant against INH in Tabriz was 15%, RIF 5%, SM 19% and EMB 2% by proportion. The highest resistance to first-line drugs was seen in Tehran. Conclusions: In conclusion, this systematic review summarized the prevalence and distribution of first-line anti-tubercular drug resistance of M. tuberculosis in Iran. Our results suggested that effective strategies to minimize the acquired drug resistance, to control the transmission of resistance and improve the diagnosis measures for TB control in Iran.